An Alternative Solution to Lifting the Ban on Doping: Breaking the Payoff Matrix of Professional Sport by Shifting Liability Away from Athletes. Issue 1 (2nd January 2017) - Camporesi, Silvia
Abstract: The persistence of doping in professional sports—either by individuals on an isolated basis and by whole teams as part of a systematic doping programme—means that professional sport today is rarely if ever untainted. There are financial incentives in place that incentivise doping and there are data that show that doping is often a systematic, organised enterprise (either at team-level, or at state-level). The main question to be answered today in professional sports is whether doping's repressive anti-doping policies do not have greater negative consequences for society. Whilst some have suggested legitimising safe doping under medical control, in this paper, I argue that doing so will do little to prevent clandestine use of dangerous performance-enhancing substances, and suggest an alternative solution to lifting the ban on doping, i.e. starting from extending liability for doping in sport beyond athletes to those holding power and authority over athletes, to changing winning incentives for doping, to making sport sustainable in the longer time by devising ways of providing athletes with a steady income which is not linked to record breaking or sponsorships.